THE ROLE OF THE SOCIAL SECURITY ADMINISTRATION AGENCY (BPJS) FOR EMPLOYMENT IN INCREASING PARTICIPATION IN THE INFORMAL SECTOR IN PINRANG REGENCY - Andi Kireyna Nasda; Herlina Sakawati; Muhammad Nur Yamin; Putri Dzakilla Handayani (Jurnal Aktor, 2026)
The Role of the Social Security Organizing Agency (BPJS) Employment Pinrang Branch Office in Increasing Informal Sector Participation, Especially Traders in Pinrang Regency. Faculty of Social Sciences and Law, Makassar State University. Supervised by Muhammad Yamin and Herlina Sakawati. This study aims to determine the Role of the Social Security Organizing Agency (BPJS) Employment Pinrang Branch Office in Increasing Informal Sector Membership Especially Traders in Pinrang Regency. this research uses a qualitative approach and produces descriptive data. Data collection is done by means of observation, interviews, and documentation, then analyzed using three stages, namely data reduction, data presentation, and verification. The results showed that BPJS Ketenagakerjaan Pinrang Branch Office has played a role in increasing membership of the informal sector, especially traders in Pinrang Regency, although it is not yet fully optimal. There are 4 indicators that are taken into consideration in seeing how the role of the Employment BPJS in increasing membership according to Emile Durkheim's theory (1999), namely, the role as an informator, the role as a facilitator, the role as an organizer, and the role as an evaluator, as for some obstacles faced by the Pinrang Branch Office Employment BPJS, namely the lack of employees which results in the provision of information or socialization is not often carried out, then the Pinrang Branch Office Employment BPJS in carrying out its role as a facilitator is still not well implemented, has not provided much access to information, and the facilities provided are still limited to one type only.